A 120-year record of the spatial and temporal distribution of gravestone decay and acid deposition. (February 2016) - Mooers, Howard D.; Cota-Guertin, Avery R.; Regal, Ronald R.; Sames, Anthony R.; Dekan, Amanda J.; Henkels, Linnea M.
Abstract: This investigation examines the spatial and temporal variability of marble gravestone decay throughout West Midlands County and adjacent portions of Warwickshire, Staffordshire, and Worcestershire. Gravestone decay has been used effectively as a quantitative measure of acid deposition. Numerous techniques have been used to assess gravestone decay and each is subject to different sources of error. To minimize error we focus only on marble gravestones that use the flush lead lettering technique. Decay of the marble leaves the lead lettering raised above the surface, and the distance can be measured with the use of a digital micrometer. Gravestone decay can be used to quantify the spatial and temporal distribution of acid deposition. Our gravestone decay database consists of 1417 individual measurements on 591 tombstones in 33 cemeteries and covers the period from 1860 to 2010. Sites range from industrial and residential areas to rural settings. These data allow us to establish the natural background rates of decay, the effects of urban/residential expansion, and the efficacy of environmental regulations. Decay rates vary from a minimum of 0.2 mm/century in remote rural areas to nearly 3.0 mm/century in the Birmingham City Center. The data are corrected for environmental variables, converted to acid deposition rates, and plotted at 10-year intervals from 1890 to 2010. Highlights: Gravestone decay is used to quantitatively reconstruct historical acid deposition. Spatial variability in gravestone decay reflects changing land use patterns. Up to 98% decrease in acid deposition after 1975 because of air quality regulation.